Response of RF-sputtered MoS2 composite films to LEO space environment. (October 2017) - Gao, Xiaoming; Hu, Ming; Sun, Jiayi; Fu, Yanlong; Yang, Jun; Liu, Weimin; Weng, Lijun
Abstract: The rf-sputtered MoS2 -Au composite films were exposed in real low earth orbit (LEO) space environment by a space environment exposure device (SEED) aboard China Shenzhou-7 manned spaceship. The ability of the composite films resistant to atomic oxygen (AO) was investigated using X-ray photoelectron spectroscope (XPS), X-ray diffraction (XRD) and field emission scanning electron microscope (FESEM) equipped with an X-ray energy dispersive spectroscopy (EDS). The results showed that the microstructure of the composite film was densified because the growth of MoS2 platelets was suppressed to some content due to the addition of Au, although it was still characterized by a typical dendrite-like morphology. No obvious change in the morphology, phase structure, element composition and friction property was observed from the space exposed and non-exposed composite films, indicating that the composite film exhibited a better anti-oxidation ability as exposed in LEO environment. The improved anti-oxidation ability was attributed to the more compact microstructure and a passivation effect that the dangling bonds at the edge planes of MoS2 platelets were probably occupied by the partial doping atoms. Highlights: The growth of MoS2 platelets was suppressed to some content due to the dopant, resulting in the densification of the sputtered MoS2 composite film. Platelet and films were exposed in low earth orbit (LEO) environment. The composite film exhibited a much better anti-oxidation ability as exposed in LEO environment. The friction property of the composite film was almost not influenced by the LEO exposure.